Load effect on the strength characteristics of restored tooth using glass fiber posts (experimental research) (Эндодонтия Today)
There are different forms of fiber glass posts to restore the anatomical shape of the tooth. It is more reasonable to use those which more repeat the shape of the root canal. So we have carried out an attempt to justify the use of intra root anatomic tab to restore the tooth coronal part, made of glass fiber post and nano-composite. A compression test and study samples of resistance to vertical and the angular 14° size 440 N (45 kg) of the load on a standard glass fiber posts - a group PI (n =7 ) and individually made anatomical tab - group PII (n = 7), reinforced fiber glass pin. To detect the defects after the experiment the thin sections of teeth (thickness 3,0 mm) were studied under nuclear and power microscope (СММ 2000). It has been established that there is a more expressed resistance to the to the angular loading of anatomic posts.